Internal Resources of Dairy Cattle Farming Business and Their Effects On Institutional Performance and Business Development - Amam, Amam; Jadmiko, Mohammad Wildan; Harsita, Pradiptya Ayu; Yulianto, Roni (ANIMAL PRODUCTION, 2019)
The purpose of this research was to identified the internal resources of dairy cattle farming business and assess their effects on institutional performance of the business risk aspects. The research was conducted at the Kawasan Pengembangan Sapi Perah Nasional (KPSPN), Malang District, East Java Province. Respondents of this reserach were all of the dairy cattle farmers who were members of the KUB (Kelompok Usaha Bersama) of the Tirtasari Kresna Gemilang. Generally, the respondent of this study was 174 person. Data were analyzed using the method of PLS (Partial Least Square). The results showed that internal resources had an effect on institutional performance by 23,4%, while business risk aspects were influenced by internal resources and institutional performance by 54,7%. Conclusion of the study was the internal resources of dairy cattle farming business consist of financial resources, technological resources and physical resources.